Harmony of Ecological Development in the Conditions of the Circular Economy - Марич, Максим; Olena, Kryvda; Svitlana, Tulchynska; Serhii, Smerichevskyi; Nataliia, Lagodiienko; Aysel, Naghiyeva (Environment and Ecology Research, 2022)
The research is devoted to the actual problem of harmony of ecological development in the conditions of the circular economy formation. The aim of the study is to develop methodological principles for determining harmony of the environmental development in the circular economy formation. To achieve this goal, the main principles of the concept of circular economy were identified, a step-by-step methodological approach to assessing harmony of the environmental development was developed and the proposed developments were tested on the example of the regions of Ukraine. Harmony of ecological development of regions in the conditions of the circular economy formation gives a chance to define a certain balance of the condition of environment that further provides development of directions of circular economy for reception of bigger efficiency of economic and ecological processes. In order to determine harmony of ecological development of regions in the conditions of the circular economy formation, it is offered to define the integrated index of ecological development, and on its base to calculate harmony of ecological development. To determine harmony, it is proposed to apply the "golden section" method using a modified formula of the hyperbolic Fibonacci cone. According to the results of the analysis, the regions are grouped depending on the level of the ecological development harmonization. Calculated and presented data on harmony of ecological development in the circular economy formation demonstrate that the highest average value of harmony have: Odessa ( = 0.402), Lviv ( = 0.349), Khmelnytsky ( =0.347), Zhytomyr ( = 0.343), Ivano-Frankivsk (= 0.343) regions. The regions with the lowest level of harmony are Dnipropetrovsk ( = 0.248), Donetsk ( = 0.157), Transcarpathian ( = 0.156), Luhansk ( = 0.143), Kherson ( = 0.171) regions. It is suggested within the study that not necessarily a high value of the integrated index of ecological development guarantees a high value of harmony of ecological development in circular economy, and vice versa.
Keywords: Ecological Development; Circular Economy; Harmony; Development; Environment; Resources